Approximate Query Processing: No Silver Bullet - Chaudhuri, Surajit; Ding, Bolin; Kandula, Srikanth (Proceedings of the ACM SIGMOD International Conference on Management of Data (SIGMOD 2017), 2017)
In this paper, we reflect on the state of the art of Approximate Query Processing. Although much technical progress has been made in this area of research, we are yet to see its impact on products and services. We discuss two promising avenues to pursue towards integrating Approximate Query Processing into data platforms.